Declining Trend of Folk Art in West Bengal: Preserving and Celebrating West Bengal's Vanishing Folk Art (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper basically deals with the most obsolete folk art of west Bengal, which are not possible to reestablish again either helping by government of by any N.G.O. Folk artist is nourished by a deferent kind of cultural background. They use different kind of instruments and they are getting trained by generation to generation. That important characteristic makes them different from others. Folk artist is famous and much more popular for their fineness of work and for structural beauty created by their hand can easily demand for a new creation. But in modern time we judge a architecture by its uniqueness or by the distinction of style or shine of the artist, which is not applicable to the folk artist .worldwide a huge number of creation of folk sculpture ( vaskorjo ) who made this is unknown to all .Those great artist who left their impression of art on a sandy pot,,a piece of memento of god and goddess, sandy design, wooden decorated a small piece,, a single pot art, metal designed statue, designated ancient manuscript or a book cover, or a drawing mud wall which is not unique all the time but a sample of their daily and very naturally a beautiful life style.